2022
DOI: 10.31083/j.fbe1401001
|View full text |Cite
|
Sign up to set email alerts
|

Autism and associated disorders: cannabis as a potential therapy

Abstract: Autism spectrum disorder (ASD) is a group of disabilities with impairments in physical, verbal, and behavior areas. Regardless the growing frequency of autism, no medicine has been formed for the management of the ASD primary symptoms. The most frequently prescribed drugs are off-label. Therefore, there is necessity for an advance tactic for the treatment of autism. The endocannabinoid system has a central role in ruling emotion and social behaviors. Dysfunctions of the system donate to the behavioral deficits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(34 citation statements)
references
References 290 publications
0
33
0
1
Order By: Relevance
“…from infancy to adulthood) and are accompanied by changes in CB1R activity in the amygdala, hippocampus, and dorsal striatum – all areas that contribute to socio-emotional processing (Servadio et al, 2016 ). While pharmacological intervention with URB597 or PF-3845 to modulate AEA reversed social impairments, FAAH inhibition also increases PEA and OEA, enhancing the activity of hippocampal CB1Rs and effecting cognition (Babayeva, Assefa, Basu, & Loewy, 2022 ; Kerr et al, 2013 ; Kerr, Gilmartin, & Roche, 2016 ; Servadio et al, 2016 ; Trezza et al, 2012 ; Trezza & Vanderschuren, 2008 ). In sum, the VPA models replicate data in other ASD animal models linking AEA signaling and social functioning and expand what is known by providing important considerations regarding the impact of development on AEA modulation.…”
Section: Autism Spectrum Disordermentioning
confidence: 99%
“…from infancy to adulthood) and are accompanied by changes in CB1R activity in the amygdala, hippocampus, and dorsal striatum – all areas that contribute to socio-emotional processing (Servadio et al, 2016 ). While pharmacological intervention with URB597 or PF-3845 to modulate AEA reversed social impairments, FAAH inhibition also increases PEA and OEA, enhancing the activity of hippocampal CB1Rs and effecting cognition (Babayeva, Assefa, Basu, & Loewy, 2022 ; Kerr et al, 2013 ; Kerr, Gilmartin, & Roche, 2016 ; Servadio et al, 2016 ; Trezza et al, 2012 ; Trezza & Vanderschuren, 2008 ). In sum, the VPA models replicate data in other ASD animal models linking AEA signaling and social functioning and expand what is known by providing important considerations regarding the impact of development on AEA modulation.…”
Section: Autism Spectrum Disordermentioning
confidence: 99%
“…Cannabis has a wide range of clinical applications and the list of diseases in which cannabis/cannabinoids are used as a treatment is constantly increasing. Studies in experimental models and humans have suggested anti-inflammatory, neuroprotective, anxiolytic, and antipsychotic properties of chemicals extracted from cannabis [ 4 ]. Cannabis contains more than 100 cannabinoids, where CBD and THC are the subjects of most studies [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…CBD decreases THC psychoactivity and exhibits anti-inflammatory, antioxidant, anticonvulsant, and neuroprotective effects [ 6 , 9 , 10 , 11 ]. CBD (Epidiolex) has been FDA and EMA approved for Dravet and Lennox–Gastaut syndromes [ 4 ]. Another cannabis medication, Sativex (THC:CBD, 1:1 ratio), is used to treat symptoms of multiple sclerosis [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We invite our readers to update their general views by reading, for example, the following review papers by Kirkland et al (2022) and Bilbao and Spanagel (2022). Remarkably, the majority of these reviews published in 2022 (about 15%) discuss the therapeutic role of CBD in autism spectrum disorders (ASD), revealing an emerging trend (Aishworiya et al, 2022;Babayeva et al, 2022;Brignell et al, 2022;Colizzi et al, 2022;de Camargo et al, 2022;Dias-de Freita et al, 2022;Pedrazzi et al, 2022;.…”
mentioning
confidence: 99%